Innovation of Smart Baby Care in Educating Postpartum Mothers on Newborn Care - Maryatun, Maryatun; Indarwati, Indarwati; Setiyanto, Sigit; Nurhayati, Asti; Rochmah, Irma Nuur (International Journal of Public Health Excellence (IJPHE), 2025)
level of knowledge and skills she has. Prima para mothers or mothers who have just given birth for the first time often do not understand about newborn care. A mother's success in raising a baby is greatly influenced by the level of knowledge and skills she has. Prima para mothers or mothers who have just given birth for the first time often do not understand about newborn care. The results show that the ease of application achieved a score of 65.9%, suitability of content 69.4%, completeness reached a score of 58.8%, suitability of desired knowledge needs 52.9% and help make it easier to understand maintenance science reached 70%. Simpulan Aplikasi SBCMomBoby dapat dengan mudah The application is used, appropriate for baby care content, comprehensive, and facilitates understanding of baby care knowledge. However, it does not fully meet the desires of postpartum mothers regarding certain knowledge that has not been included in the SBC MomBaby application.